KEJAHATAN TRANSNASIONAL PENYELUNDUPAN NARKOBA DARI MALAYSIA KE INDONESIA: KASUS DI PROVINSI KEPULAUAN RIAU DAN KALIMANTAN BARAT - Simela Victor Muhamad (Jurnal Politica, 2015)
Drugs smuggling organized by international syndicates into Indonesia tends to increasingly intensity. This can occur since Indonesia is a potential and profitable market. International syndicates with its cross-border networks and various methods, continues to smuggle its drugs into Indonesia. As form of transnational crime, drugs smuggling into Indonesia cannot be tolerated, thus, effective efforts must be found to handle it. This article, as part of the 2014 research report, discussed these issues, which focuses drugs smuggling, primarily to the Province of Riau Islands and West Kalimantan, two areas bordering Malaysia and vulnerable from drugs smuggling.